FAKTOR-FAKTOR YANG MEMPENGARUHI OPINI GOING CONCERN: STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA - Lely Kumalawati (Jurnal Akuntansi dan Ekonomi Bisnis PSDKU kediri, 2012)
The aim of this research is to find evidence about factors affected to going concern opinion. Those factors are opinion shopping, audit quality, financial distress, audit opinion, and firm growth. Sampling method using purposive sampling, and find 71 manufacturing companies listed in Indonesian Stock Exchange as sample companies. The data analysis of this research used logistic regressin. The hypothesis testing find that financial distress and audit opinion affected to going concern opinion. This result show that auditor inclined to give going concern opinion when the probability of firm bankruptcy getting higher, and auditor is not easily give unqualified opinion for the next period base on consideration of going concern opinion in the previously period. This research didn’t find the influence of opinion shopping, audit quality, and firm growth to going concern opinion. This result shows that auditor switching is estimated to give better opinion than previously auditor, so auditor’s independencies are very doubted. Auditor can’t guarantee the auditee not to receive going concern opinion although the sales ratio is increase.